2017
DOI: 10.1186/s13148-017-0406-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome alterations in aortic valve stenosis and its related left ventricular hypertrophy

Abstract: Aortic valve stenosis is the most common cardiac valve disease, and with current trends in the population demographics, its prevalence is likely to rise, thus posing a major health and economic burden facing the worldwide societies. Over the past decade, it has become more than clear that our traditional genetic views do not sufficiently explain the well-known link between AS, proatherogenic risk factors, flow-induced mechanical forces, and disease-prone environmental influences. Recent breakthroughs in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 162 publications
(237 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, transfection of porcine activated VICs with miR-141 resulted in the recovery of physiological signaling of other regulators of valve calcification, bone morphogenic protein-2 (BMP-2) and ALP [ 77 ]. Since VICs respond to mechanical signals of the surrounding ECM, miRNAs interfering with calcific crystal deposition might represent potent therapeutic tools [ 78 ]. Another mechanism by which epigenetics exerts its control is DNA methylation, usually associated with gene expression silencing [ 18 ].…”
Section: Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transfection of porcine activated VICs with miR-141 resulted in the recovery of physiological signaling of other regulators of valve calcification, bone morphogenic protein-2 (BMP-2) and ALP [ 77 ]. Since VICs respond to mechanical signals of the surrounding ECM, miRNAs interfering with calcific crystal deposition might represent potent therapeutic tools [ 78 ]. Another mechanism by which epigenetics exerts its control is DNA methylation, usually associated with gene expression silencing [ 18 ].…”
Section: Valvesmentioning
confidence: 99%
“…Another solution to overcome the adverse remodeling of cell-free valve implants could be to directly modulate the activity of genes involved in cell mechanosensation and thus reduce the intracellular transmission of mechanical cues, thereby reducing the transition of cells toward a matrix remodeling and compacting phenotypes. Examples may include the employment of materials with finely tuned viscoelastic properties to maintain a relatively low level of intracellular stress fiber tensioning [ 78 , 79 ] or delivering drugs interfering with downstream effectors of the mechanically-activated signal transduction cascades, e.g., the Hippo-dependent transcriptional pathway [ 101 ] ( Figure 2 ). Interestingly, it has been found that NOTCH signaling reactivation is required for cardiac valve regeneration in the zebrafish model [ 102 ].…”
Section: Valvesmentioning
confidence: 99%
“…Several functional studies have indicated that epigenetic mechanisms play an important role in the initiation and progression of aortic stenosis as well as LVH. These mechanisms could contribute to endothelial dysfunction, disease-prone activation of monocytes and macrophages, and osteogenic transdifferentiation of aortic valve interstitial cells, leading to valvular inflammation, fibrosis, calcification, and pressure overload-induced maladaptive myocardial remodeling and LVH [30]. Villar, et al reported that the regression of hypertrophy at 1-year after release of pressure overload is related to the preoperative myocardial expression of remodeling-related genes.…”
Section: Overall (N ═ 97)mentioning
confidence: 99%
“…In contrast, LncRNAs are more than 200 nucleotides long and can localize to different sub-cellular depots ( 152 ). While there are limited studies on the epigenetic regulation of cardiogenesis and valvulogenesis ( 153 155 ), gene methylation status, and LncRNAs and MiRs profiles have shown to be altered in CAVD and aortic stenosis and these are summarized in Tables 1 , 2 , respectively ( 181 183 ).…”
Section: Epigenetic Regulation Of Aortic Stenosis and Calcific Aorticmentioning
confidence: 99%